Pelaksanaan Pengawasan Barang Terkait Keamanan,Keselamatan, Kesehatan, dan Lingkungan Hidup (K3L) Tahun 2020 - Kusdarwati, Eny (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2021)
The government has tried to prevent the widespread circulation of imported products resulting from free trade. One of the measures taken by the Government is the issuance of a mandatory Indonesian National Standard (SNI) policy. However, not all goods circulating in the territory of Indonesia are subject to mandatory SNI, the government has issued a policy to regulate these goods. Policies governing traded goods that have not been implemented by SNI must be regulated in Constitution Number 7 of 2014 concerning Trade in article 32 paragraph (1) and the sanctions in Constitution Number 11 of 2020 concerning Job Creation, as well as its derivative regulations for registering goods related to Security,.Safety,.Health,.and.the Environment (K3L) to the..Minister. This policy has been in effect since August 14, 2019, not all businessmen who trade goods related to K3L have complied with the policy. The goal of this research was to find out the level of compliance of businessmen with application of licensing for registration of goods related to K3L based on the results of supervision of goods related to K3L conducted by the Directorate of Trade Order in 2020. The research was carried out using index calculations compliance of businessmen with Cooke's method. Based on the results of the study, it is known that the compliance of businessmen with regulations for registration of goods related to K3L is still low because many violations are still found due to the ignorance of businessmen to these regulations. Thus, it is necessary to increase socialization activities to businessmen and consumers, as well as to expand the supervision area in the following year.